ОPTIMIZATION METHOD OF PREPARATION IN CARRYING OUT LAPARASCOPIC INTESTINAL SURGERY IN GYNECOLOGICAL PATIENTS - Громова, А.А.; Нестеренко, Л.А.; Мартиненко, В.Б. (World of Medicine and Biology, 2015)
Today laparascopy is a current method , and widely using in general surgery and gynecology. Especially effective laparacopy used in the treatment of many gynecological diseases ,like endometriosis ,tumor of uterus and ovary ,allowing deprive patients from long-term treatment. Perform gynecological operations with laparoscopic access depend anatomically close a small and large intestines wich connected with pathological processus of inflammation of femal genital system ,endometriosis ,adhesive disease of abdominal cavity and athers. Also the cause of occupying lesions of small pelvis can be pathology of digestive system. Because of that to exept this pathology fibro-oesophago-gastroscopy and colonoscopy are recommendated . For laparascopic operations it is necessary the absence of abdominal loops. Imposition of pneumoperitoneum is one of the important stage of laparascopy. Introduction of gaz to the abdominal cavity is necessary for increase volume and create free space between anterior abdominal wall and intestin ,and necessary for moving tools and improve conditions for inspection. Usully ,adequant preparation of intestin of patient before the laparascopic intervention is obligatory. Starvation before the operation is not recommedeted ,because it promotes metabolic acidosis and disorder of metabolism after operation. Now 2 forms of intestinal preparation formed before the operation. The first is complete refusion for any preparation ,if a direct intervention on intestin is not planed. Second preparation perfomed in all situations. In gynecological surgery enought during 3 days , before the operation respect regime: morning light breakfast,lunch- liquid ,diner- sweet tea. A different ways are using to preparate the intestшn before operation. This tradional ways contents : no slag diet ,intestinal cleaning , intake of laxatives ,lavage of stomac and intestin. But practic proved ;that traditionnel method not always justify themselves by some drawbacks. No slag diet create favorable conditions for release thin intestin, but not always. With help of intestinal cleaning it is possible to acquire releasing the distal level of large intestin. In the study of effective traditionnel preparation in stationary conditions proved that complete absence intestinal contenant can be attempt in 29-37% cases. Irrigational lavage of intesten manitol and salt solution- difficult in this method , wich will be hard for patient and probable complications related with hydroelectoltis disorders and has a many contradictions. So in modern medicine, it is solely a historical perspective. advanced bowel cleansing prior to various manipulations ,including surgery- preparation with drugs contening polyethilenglicol. purpose of this study - determination optimal method preparation before operation of intestin for gynecological patients with traditionnel methods and with using substances contenting polyethilenglycol. Methods of investigation - clinico-laboratorial ,subjective and objective methods. Materials – examined 97 woman age from 20 to 45 years with different gynecological diseases, need surgical laparascopic treatment. At admission to depatement all woman before the operation taked complexe of clinical and laboratorial examinations. For 2 of them mioma with adenomiosis identificated ,for 14- mioma of uterus,for 48- cystoma of ovary and 33-woman infertility caused by tubal factor. All the precedent woman were separated to 2 groupes. I groupe made 52 woman who during 3 days of preparation of intestin used no slag diet. Preferably eat low-fat broth ,fish,cheez ,cereal and yogurt. Patients taking before surgery drugs contented polyethilenglicol in next shema one bag (64g) dissolved in 1l of cold ,boiled water. For completly emptied intestin , necessary 3-4 bags near 3-4 litres solution. After lunch ,patient , every 15 min taked by 1 cap of prepared solution. For all patients during 4-5 hours folowed 5-7 defecations. All patients without exeption good moved drugs. No disorder of general stats of women. II groupe control mad 45 woman , who before operation during 3 days of preparation of intestin comply no slag diet. On the eve of operation ,at afternoon comply intestin cleaning (1.5 L solution). Efficacity of preparation of intesten before the operation ,on both groups of patients , estimated during operation- conducted revision of the abdominal cavity. For that woman OG 100% detected absence of gaz in intestin and his complete discharging , and it contributed confortable work of surger. Practically indicators of hemoglobin dont change , electrolitis ,heamatocryt and biochemical indicators of protein , nitrogen and carbohydrates consistence of blood plasma. Dynamic of ECG dont change. All this testify that ,using macrolids drugs for preparation of intestin before the operation for patients dont cause changement of homeostasis and heamodynamic. For 42 woman CG(93%) , in time of Review laparascopy , installed complete discharging of intestin. Preferences of preparation of intestin before the operation , for gynecological patients , when using drugs content polyethilengol , cause of simplecity of processus. Patients prepared themself at home. It is no obligatory the participation of medical personnel during processus. Conclusion : proving that preparation of intestin before the operation for gynecological patients before laparascopy , drugs content polyethilenglicol , is an optimal and effective method.